Deep Brain Stimulation in Persistent Vegetative States: Ethical Issues Governing Decision Making - Sara Patuzzo; Paolo Manganotti (Behavioural Neurology)
The aim of the present paper was to investigate the fundamental ethical issues of Deep Brain Stimulation (DBS) on patients remaining in Persistent Vegetative State (PVS). First, the purpose of this analysis was to discuss the nature of this intervention in order to classify it such as an ordinary clinical practice, or otherwise as an extraordinary clinical practice or as experimental research. Second, ethical issues, criticisms, and methodological issues of this intervention, also in the future perspectives, are discussed, attempting to identify who could give informed consent for a patient in PVS.